1981
DOI: 10.2118/8813-pa
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of CO2 and Crude Oil in Low-Temperature Reservoirs

Abstract: Phase behavior of CO2/Crude-oil mixtures which exhibit liquid/liquid (L/L) and liquid/ liquid/vapor (L/L/V) equilibria is examined. Results of single-contact phase behavior experiments for CO2/separator-oil mixtures are reported. Experimental results are interpreted using pseudoternary phase diagrams based on a review of phase behavior data for binary and ternary mixtures of CO2 with alkanes. Implications for the displacement process of L/L/V phase behavior are examined using a one-dimensional finite differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 23 publications
8
75
0
Order By: Relevance
“…At equilibrium, when the stirrer was still on, it was observed that there was a layer of oily liquid above the black crude oil rotating with the stirring, which also confirmed the existence of the second liquid phase. Similar liquid-liquid split has been seen in the experiments performed by Orr et al [13]. In their experiments, as the CO2 pressure was increased, a second liquid phase appeared on top of the oil rich phase.…”
Section: Phase Behavior Measurementsupporting
confidence: 83%
See 1 more Smart Citation
“…At equilibrium, when the stirrer was still on, it was observed that there was a layer of oily liquid above the black crude oil rotating with the stirring, which also confirmed the existence of the second liquid phase. Similar liquid-liquid split has been seen in the experiments performed by Orr et al [13]. In their experiments, as the CO2 pressure was increased, a second liquid phase appeared on top of the oil rich phase.…”
Section: Phase Behavior Measurementsupporting
confidence: 83%
“…The phase boundaries are determined by the crude oil composition, since CO2 extracts the light and intermediate components in the crude oil to generate a second liquid phase on top of the oil rich phase [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…2.1-2 to 2.1-4 are quite similar to those reported previously for other Permian basin oils ( Orr et al 1981, Orr andJensen 1984), despite the fact that the Means crude oil is somewhat heavier than oils examined previously(see Section 2.2 for a detailed comparison of the composition of several Permian basin oils). That result is consistent with the idea that a three-phase region will appear at temperatures above the critical temperature of CO2 only if sufficient quantities of extractable hydrocarbons are present in the oil.…”
Section: Discussionsupporting
confidence: 85%
“…When the pressure is beyond the saturation point of CO2, 64 bar, the CO2 is in the liquid phase and we have a Liquid-Liquid (L-L) system. The phase change phenomena mentioned above have also been reported by Orr et al in their study of the phase behavior of CO2 with crude oil and with alkanes [13].…”
Section: Resultssupporting
confidence: 73%